Handbook of writing research - MacArthur, Charles A.; Graham, Steven 1950-; Fitzgerald, Jill (New York The Guilford Press, 2016)
"The definitive reference in the field, this volume synthesizes current knowledge on writing development and instruction at all grade levels. Prominent scholars examine numerous facets of writing from sociocultural, cognitive, linguistic, neuroscience, and new literacy/technological perspectives. The volume reviews the evidence base for widely used instructional approaches, including those targeting particular components of writing. Issues in teaching specific populations, ncluding students with disabilities and English learners, are addressed. Innovative research methods and analytic tools are clearly explained, and key directions for future investigation identified."--Page 4 de la couverture.
"Subject Areas/Keywords: cognitive, Common Core standards, CCSS, Common Core State Standards, composition, difficulties, elementary, English language learners, genres, linguistics, literacy, new literacies, professional development, reading, research methods, secondary, sociocultural, teaching methods, theories, writers, writing development, writing instruction DESCRIPTION The definitive reference in the field, this volume synthesizes current knowledge on writing development and instruction at all grade levels. Prominent scholars examine numerous facets of writing from sociocultural, cognitive, linguistic, neuroscience, and new literacy/technological perspectives. The volume reviews the evidence base for widely used instructional approaches, including those targeting particular components of writing. Issues in teaching specific populations--including students with disabilities and English learners--are addressed. Innovative research methods and analytic tools are clearly explained, and key directions for future investigation identified"--R?esum?e de l'?editeur.
What Do Sociocultural Studies of Writing Tell Us about Learning to Write? / Charles Bazerman -- Writing Research from a Cognitive Perspective / Charles A. MacArthur and Steve Graham -- Writing Research through a New Literacies Lens / Donald J. Leu, David Slomp, Lisa Zawilinski, and Julie A. Corrigan -- Writing Process Theory : A Functional Dynamic Approach / Huub van den Bergh, Gert Rijlaarsdam, and Elke van Steendam -- Understanding Planning in Text Production / Mark Torrance -- A Sociocultural Perspective on Writing Development : Toward an Agenda for Classroom Research on Students' Use of Social Practices / Richard Beach, George E. Newell, and Jennifer VanDerHeide -- After Writing, After School / Katherine Schultz, Glynda A. Hull, and Jennifer Higgs -- The Development of Multileveled Writing Systems of the Brain : Brain Lessons for Writing Instruction / Karin H. James, R. Joanne Jao, and Virginia Berninger -- From Language to Text : The Development and Learning of Translation / Michel Fayol -- From Text to Language and Back : The Emergence of Written Language / Liliana Tolchinsky -- Self-Efficacy Beliefs and Motivation in Writing Development / Roger H. Bruning and Douglas F. Kauffman -- Self-Regulation and Writing : Meta-Analysis of the Self-Regulation Processes in Zimmerman and Risemberg's Model / Tanya Santangelo, Karen R. Harris, and Steve Graham -- Relationships between Reading and Writing Development / Timothy Shanahan -- Evidence-Based Practice and Writing Instruction : A Review of Reviews / Steve Graham, Karen R. Harris, and Amber B. Chambers -- New Developments in Genre-Based Literacy Pedagogy / David Rose -- Writing to Learn / Perry D. Klein, Nina Arcon, and Samanta Baker -- Sociocultural Approaches to High School Writing Instruction : Examining the Roles of Context, Positionality, and Power / Michelle Nguyen Kwok, Exequiel Ganding III, Glynda A. Hull, and Elizabeth Birr Moje -- Instruction in Evaluation and Revision / Charles A. MacArthur -- Grammar Instruction / Richard Hudson -- Argumentative Writing / Ralph P. Ferretti and Yueyue Fan -- Computer-Based Writing Instruction / Laura K. Allen, Matthew E. Jacovina, and Danielle S. McNamara -- The Role of Professional Development for Enhancing Writing Instruction / Sarah J. McCarthey and Cristin M. Geoghegan -- Writing Development and Instruction for Students with Learning Disabilities : Using Diagnostic Categories to Study Writing Difficulties / Vince Connelly and Julie Dockrell -- Writing Development and Instruction for English Language Learners / Alister Cumming -- Teaching Writing in Culturally and Linguistically Diverse Classrooms / Valerie Kinloch and Tanja Burkhard -- Automated Writing Evaluation : An Expanding Body of Knowledge / Mark D. Shermis, Jill Burstein, Norbert Elliot, Shayne Miel, and Peter W. Foltz -- Keystroke Logging in Writing Research : Analyzing Online Writing Processes / Luuk Van Waes, Mari?elle Leijten, Eva Lindgren, and ?Asa Wengelin -- Linguistic Analysis Tools / Pablo Pirnay-Dummer.
Prof. Ma. Theresa Tabada (Recommending faculty) - Bookfair2017
Comprend des r?ef?erences bibliographiques et des index.
Keywords: English language -- Rhetoric -- Study and teaching -- Research -- Handbooks, manuals, etc; English language -- Composition and exercises -- Research -- Handbooks, manuals, etc; Report writing -- Study and teaching -- Research -- Handbooks, manuals, etc; Language arts -- Research -- Handbooks, manuals, etc